Protein levels with and without Monensin for finishing steers - W. Thompson; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1979)
Ration erode protein levels of 9%, 11%, 15%, 12 declining to 10.5% and 13% declining to 11% and finally to 9% were fed with and without Monensin. Steers fed 9% protein continuously gained the least and were the least efficient. Steers fed the other four protein levels had similar performances. Averaged across protein levels, Monensin had no significant effect on steer performance but it improved feed efficiency 7.4% with the 11%, 12-10.5% and 13-11-9% rations.
Keywords: Cattlemen& #x27; s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Protein; Monensin; Steers